Certification Program for Micro, Small, and Medium Enterprise Products Halal Seafood: Training and Mentoring in Sukolilo Baru Subdistrict, Surabaya - Ardhanari, Margaretha; Nugrohadi, Gratianus Edwi (LPPM Universitas Ma Chung, 2024)
The seafood processing business group in Sukolilo Baru, Kenjeran, Surabaya consists of 43 units. Among these, 29 units are household-scale seafood processing businesses and seafood product retail shops. Following the Covid-19 pandemic, these entrepreneurs are striving to restore their businesses' turnover to pre-pandemic levels. Hence, they require training and mentoring as a follow-up to the community service program previously conducted by the community service team. The achievements of the team's previous community service program include: improved product packaging skills, labeling and branding of products, as well as the issuance of Business Identification Numbers (NIB) and suitability certifications for household-scale businesses to the entrepreneurs. The ongoing community service activities currently include training, mentoring, and halal certification registration. These activities aim to enhance the marketability of the partners' products. The partners in this community service endeavor are residents in the area engaged in seafood processing businesses. Participants are involved in three activities: pre-community service preparation, community service implementation, and post-community service follow-up (monitoring-evaluation). Preparation activities are realized through preliminary studies involving pre-surveys to evaluate the conditions and readiness of the entrepreneurs. Implementation activities include: (1) training on the importance of halal certification, (2) mentoring and practice in filling out halal certificate registration forms using the Si Halal application, BPJPH Kemenag, and (3) evaluation of the process of these activities. This evaluation is conducted to understand the extent of understanding of halal certification for Micro, Small, and Medium Enterprises (MSMEs).